Exposure of children in Serbia to potentially harmful excipients when treated with approved antibiotics - Puača Gorana G.; Todorović Nemanja B.; Čanji Jelena M.; Bajić Dejana D.; Vesković Dunja M.; Pavlović Nebojša N.; Ilić Snježana Đ.; Lalić-Popović Mladena N. (Srpsko lekarsko drustvo, 2021)
Introduction: According to current understanding of the role of excipient in medicines, they could not be considered as completely pharmacologically inert substances. Although excipients do not have the potential to cause adverse drug reactions (ADRs) in most patients, some of their negative effects have been established. Special caution regarding excipients intake is advised, especially in vulnerable populations such as pediatric one. Aim: The aim of this paper was to investigate the exposure of children on antibiotic therapy to excipients with known effects (EKE). Methods: During a one-month period antibiotic prescriptions data were taken from community pharmacies in Novi Sad, Serbia. Age, diagnosis and prescribed therapy were observed. Data about qualitative content of prescribed medicines were taken from Summaries of Product Characteristics (SmPC) available at the official website of Medicines and medical devices agency of Serbia (ALIMS). Excipients were considered to be potentially harmful if they were listed in European Medicines Agency (EMA) guidelines. Results: The most commonly observed diagnosis was a respiratory infection, which affected more than 88% of children prescribed with an antibiotic. Only 5 out of 33 prescribed antibiotic formulations did not contain at least one EKE. Prescribed medicines mostly contained sodium compounds (77.78%), sucrose (34.07%) and sodium benzoate (31.11%). In addition, the following EKE were detected: propylene glycol, aspartame, sorbitol, lactose, potassium, mannitol, benzalkonium chloride, azorubine, parabens, sodium metabisulfite and sunset yellow. Around 75% of prescribed antibiotic formulations contained inappropriately labeled EKE (sodium and potassium compounds, sodium benzoate and propylene glycol). Additionally, inappropriately labeled information leaflets did not include possible adverse effects caused by the EKE. Conclusions: This paper indicates high exposure of patients to EKE, where almost all children treated with antibiotics (96.3%) were simultaneously administered at least one EKE. We confirmed that approved medicines cannot meet the treatment needs of all patients, and that inappropriately labeled medicines carry a risk of ADRs, especially in newborns. Personalized treatment is especially important in children, as the appropriate dosage forms and diversity in formulation ingredients is lacking. Knowing the type and roles of each ingredient of the medicines it is possible to formulate a preparation that will meet all the individual children's needs.